Sewage disposal ten years' experience (now fourteen years) in works of intermittent downward filtration, separately and in combination with surface irrigation, with notes on the best practice and results of sewage farming - Denton, J. Bailey 1814-1893 (E. & F.N. Spon, 1885)
Intermittent filtration was prominently referred to in the Royal Commission on Metropolitan Sewage Discharge, and so the author has updated his 1880 work 'Ten years' experience in works of intermittent downward filtration'.